Factors predicting persistence of AV nodal block in post‐TAVR patients following permanent pacemaker implantation. Issue 10 (5th September 2019) - Lader, Joshua M.; Barbhaiya, Chirag R.; Subnani, Kishore; Park, David; Aizer, Anthony; Holmes, Douglas; Staniloae, Cezar; Williams, Mathew R.; Chinitz, Larry A.
Abstract: Introduction: A common complication of transcatheter aortic valve repair (TAVR) is development of conduction defects requiring pacemaker (PPM) implantation. These defects are not universally permanent. Objective: To determine the incidence and predictors of persistent device dependency in patients with PPM implantation following TAVR with a self‐expanding prosthesis. Methods: Records of patients who underwent post‐TAVR PPM implantation were reviewed. Patients with persistent complete AV block (AVBIII) one month post‐TAVR were compared to those regaining conduction. Results: Between September 2014 and March 2017, 485 patients underwent TAVR with a self‐expanding prosthesis; 77 (15.9%) underwent PPM implantation for AVBIII. Device interrogation at one month was available for 61 patients (79%): 22 (36.1%) had resolution of AVBIII while 39 (63.9%) remained pacemaker‐dependent. Pre‐TAVR right bundle branch block was more frequent in device‐dependent patients (19 of 38, 50% vs 4 of 22, 18%; RR 2.75; P = .01). Device‐dependence was associated with AVBIII as the first postprocedural rhythm (37 of 39, 95% vs 12 of 22, 55%; RR 1.74; P < .0001), earlier implantation (median 1d, IQR: 0‐1.5d vs 2d, IQR: 1.0‐4.0d, P = .0004), and a shorter duration of hospitalization (median 3d, IQR: 2‐3.5d vs 4d, IQR: 2‐5.75d, P = .03). Pacemaker dependence was also associated with a higher prosthesis‐to left ventricular outflow tract (LVOT) diameter (1.45 ± 0.11 vs 1.39 ± 0.07; P = .02) and the lack of prior aortic valvuloplasty (5 of 39, 13% vs 8 of 22, 36%; RR 0.35; P = .03). Conclusions: In patients receiving a PPM following self‐expanding TAVR, a long‐term pacing requirement can be predicted from the timing of AV block, existing conduction‐system disease, larger prosthesis‐to‐LVOT diameter, and the lack of aortic valvuloplasty.